Acanthamoeba keratitis: risk factors and outcome. Issue 12 (December 1995) - Illingworth, C D; Cook, S D; Karabatsas, C H; Easty, D L
Abstract : AIMS/BACKGROUND–This study was initiated to investigate risk factors for and outcome of Acanthamoeba keratitis. METHODS–Results of treatment were studied in 22 patients (23 eyes) presenting to Bristol Eye Hospital between 1985 and February 1995. Details related to the use and disinfection of contact lenses were also obtained. An additional two patients who were seen at Bristol but mainly treated elsewhere were surveyed for contact lens related information only. RESULTS–The incidence of Acanthamoeba keratitis rose substantially in the 1990s: three patients presented before 1990, while the remaining 21 presented between January 1990 and February 1995. Eleven patients have presented since january 1994. All of the patients in this series were contact lens wearers, 16 (67%) using daily wear disposable contact lenses. Contact lens disinfection data were available in 22 patients of whom 11 (50%) were using chlorine disinfectant. Other types of disinfection were much less common. Four patients (18%) had not used any disinfectant. During the course of the series the average diagnostic delay has fallen markedly, although in 77% of patients a diagnosis of a viral keratitis, most commonly herpes simplex, was made on first presentation. All but three of the series were treated with a combination of polyhexamethylene biguanide and propamidine isethionate. Penetrating keratoplasty was performed in 9/23 eyes (39%); in all of these eyes diagnosis was delayed for at least 6 weeks. All but one of the eyes in the series achieved a visual acuity of 6/9 or better after treatment, and 18 eyes (78%) saw 6/6 or better. CONCLUSIONS–Most patients with Acanthamoeba keratitis can now expect a good visual result and cure by medical therapy alone is favoured by early diagnosis.